Efektivitas Bimbingan Kelompok dengan Teknik Psikodrama dalam Mengatasi Kejenuhan Belajar Siswa - Yansen Alberth Reba; Yulius Mataputun; Eka Sawitri; Habel Saud; Mikhael Udam; Sally Putri Karisma; Sirjon Sirjon; M. Zaenul Muttaqin (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study was to examine the effectiveness of group guidance with psychodrama techniques in overcoming learning saturation among university students. This mixed-method study employed an embedded design with a pre-experimental one-group pretest-posttest approach as the dominant quantitative component. The sample consisted of nine university students from the Guidance and Counseling Study Program at FKIP UNCEN, selected through purposive sampling based on high learning saturation scores from a 30-item questionnaire measured on a 5-point Likert scale. The results demonstrated a significant reduction in learning saturation levels following the psychodrama intervention, with paired t-test analysis showing a significant difference between pre-test and post-test scores (t = -4.739, df = 8, p = 0.001). Qualitative findings further revealed that students experienced improved self-control, increased relaxation, and enhanced learning motivation after participating in the psychodrama sessions. These findings indicate that group guidance with psychodrama techniques is an effective approach for reducing learning saturation among university students.